What is the sum of the following sinc series?

$$f(k,y)=\sum_{n=-\infty}^{\infty} \frac{\text{sin} \pi(kn-y)}{\pi(kn-y)}$$ where $k$ is an integer greater then zero

This question is a generalisation of What is the sum over a shifted sinc function? and not a duplicate. The former question only considers the case for $k=1$

  • $\begingroup$ Welcome to MSE. It will be more likely that you will get an answer if you show us that you made an effort. $\endgroup$ – José Carlos Santos May 5 '18 at 9:36
  • 1
    $\begingroup$ Possible duplicate of What is the sum over a shifted sinc function? $\endgroup$ – mol3574710n0fN074710n May 5 '18 at 9:40
  • $\begingroup$ As I explained this is not a duplicate but a genertalisation of math.stackexchange.com/questions/1242280/… $\endgroup$ – Daniel May 5 '18 at 10:16
  • $\begingroup$ By checking my previous answer you'll see that the series converges when $\displaystyle k \in \left(0,2\right)$. Otherwise, you can always write $\displaystyle k$ as $\displaystyle 2\left\lfloor{k \over 2}\right\rfloor + 2\left\{{k \over 2}\right\}$ for any other $\displaystyle k$-value. $\endgroup$ – Felix Marin May 5 '18 at 23:18
  • $\begingroup$ @FelixMarin I am only interested in k being an integer, and can't relate well what you are saying with what I expect. I don't think the answer is a constant, I am expecting an answer function of $k$ and $y$ $\endgroup$ – Daniel May 6 '18 at 10:04

I formulate a general solution here to compute $\sum_{n=-\infty}^{n=\infty}\frac{\sin(N\pi(y-\frac{n}{T}))}{\pi(y-\frac{n}{T})}$ for $T<N,$ with $T,N\in\mathbb{\mathbb{R}}^{+}$, and then use the case where $T=1/k$ for an integer $k>1$ and $N=1$ to show that the sum requested in this problem, $f(k,y)\equiv\sum_{n=-\infty}^{\infty}g(kn-y)=\sum_{n=-\infty}^{\infty}g(y-kn)$ for the (even) sinc function $g(y)=\begin{cases} \frac{sin\pi y}{y} & y\not\neq0\\ 1 & y=0 \end{cases}$ is equal to:

$f(k,y)=\begin{cases} k & \frac{y}{k}\in\mathbb{Z}\\ \cos(\pi y)+\frac{\sin(\pi y(1-1/k))}{\sin(\pi y/k)} & \frac{y}{k}\notin\mathbb{Z},\,k\,\mathrm{even}\\ \frac{\sin(\pi y)}{\sin(\pi y/k)} & \frac{y}{k}\notin\mathbb{Z},\,k\,\mathrm{odd} \end{cases}$

Let $W_{N}(t)$ be the rectangular window of width $N$ defined in continuous time given by $W_{N}(t)=\begin{cases} 1 & -N/2<t<N/2\\ 1/2 & |t|=N/2\\ 0 & \textrm{else} \end{cases}$ where $t$ is in units of seconds. Its Fourier transform is then the (continuous, aperiodic) sinc function: $\hat{W}_{N}(y)=\begin{cases} \frac{\sin(N\pi y)}{\pi y} & y\neq0\\ N & y=0 \end{cases}$ where the units of $y$ is hz (cycles per second). Sampling $W_{N}(t)$ at discrete intervals of $T$ seconds, yields a discrete, aperiodic signal, $w_{N}(t)=\begin{cases} 1 & -N/2<t<N/2\\ 1/2 & |t|=N/2\\ 0 & \textrm{else} \end{cases},t\in\mathbb{Z}T.$ The (continuous, periodic) Discrete Time Fourier Transform of this, $\hat{w}_{N}(y)$ can be derived as folllows:

Directly from the definition of DTFT, and making the change of variable $n=t/T$, we have $w_{N}(n)=\begin{cases} 1 & -N/2T<n<N/2T\\ 1/2 & |n|=N/2T\\ 0 & \textrm{else} \end{cases},n\in\mathbb{Z}.$

For $yT\notin\mathbb{Z}$ and $N/T$ is an even integer (implying that $N/2T$ is an integer value, and so $w_{N}(n)$ is evaluated at the endpoints), then:

\begin{eqnarray*} \hat{w}_{N}(y) & = & \sum_{n=-\infty}^{\infty}w_{N}(n)e^{-i2\pi yTn}=\frac{1}{2}\left(e^{-iN\pi y}+e^{iN\pi y}\right)+\sum_{n=-\frac{N-2T}{2T}}^{\frac{N-2T}{2T}}e^{-i2\pi yTn}=\\ & =\frac{1}{2}\left(e^{-iN\pi y}+e^{iN\pi y}\right)+ & \frac{e^{i\pi(N-2T)y}-e^{-i\pi Ny}}{1-e^{-i2\pi yT}}=\frac{e^{-i\pi yT}}{e^{-i\pi yT}}\left(\frac{e^{i\pi y(N-T)}-e^{-i\pi y(N-T)}}{e^{i\pi yT}-e^{-i\pi yT}}\right)\\ & =\cos(\pi yN)+ & \frac{\cos(\pi y(N-T))+i\sin(\pi y(N-T))-(\cos(\pi y(N-T))-i\sin(\pi y(N-T)))}{\cos(\pi yT)+i\sin(\pi yT)-(\cos(\pi yT)-i\sin(\pi yT))}\\ & = & \cos(\pi yN)+\frac{2i\sin(\pi y(N-T))}{2i\sin(\pi yT)}=\cos(\pi yN)+\frac{\sin(\pi y(N-T))}{\sin(\pi yT)} \end{eqnarray*}

(where the geometric series sum formula used above relies on the assumption that $yT\notin\mathbb{Z}$ so that $e^{-i2\pi yT}\neq1.$ )

If $N/T$ is an even integer but we now assume $yT\in\mathbb{Z}$, then we can write $y=\frac{l}{T}$ for some $l\in\mathbb{Z}$ and in this case we have that \begin{eqnarray*} \hat{w}_{N}(y) & = & \sum_{n=-\infty}^{\infty}w_{N}(n)e^{-i2\pi yTn}=\sum_{n=-\infty}^{\infty}w_{N}(n)e^{-i2\pi ln}=\sum_{n=-\infty}^{\infty}w_{N}(n)\\ & = & \sum_{n=-\frac{N}{2T}}^{\frac{N}{2T}}w_{N}(n)=\frac{N}{T} \end{eqnarray*}

If $yT\notin\mathbb{Z}$ and $N/T$ is not even, then, letting $F\equiv Floor\left[N/2T\right]$ and $R=N/Tmod2$, we have that

\begin{eqnarray*} \hat{w}_{N}(y) & = & \sum_{n=-\infty}^{\infty}w_{N}(n)e^{-i2\pi yTn}=\sum_{n=-F}^{F}e^{-i2\pi yTn}=\sum_{t=-(N-RT)/2T}^{(N-RT)/2T}\left(e^{-i2\pi yT}\right)^{n}\\ & & =\frac{e^{i\pi(N-RT)y}-e^{-i\pi(N-RT+2T)y}}{1-e^{-i2\pi yT}}=\frac{e^{-i\pi yT}}{e^{-i\pi yT}}\left(\frac{e^{i\pi y(N-RT+T)}-e^{-i\pi y(N-RT+T)}}{e^{i\pi yT}-e^{-i\pi yT}}\right)\\ & & =\frac{\cos(\pi y(N+T(1-R)))+i\sin(\pi y(N+T(1-R)))-(\cos(\pi y(N+T(1-R)))-i\sin(\pi y(N+T(1-R)))}{\cos(\pi yT)+i\sin(\pi yT)-(\cos(\pi yT)-i\sin(\pi yT))}\\ & & =\frac{2i\sin(\pi y(N+T(1-R)))}{2i\sin(\pi yT)}=\frac{\sin(\pi y(N+T(1-R))}{\sin(\pi yT)}\\ \end{eqnarray*}

(Note that in the case of $N/T$ integer valued, this gives $R=1$ and so the above would simplify to $\frac{\sin(\pi yN)}{\sin(\pi yT)}$).

If $N/T$ is not an even integer but we now assume $yT\in\mathbb{Z}$, then we again write $y=\frac{l}{T}$ and in this case we have that \begin{eqnarray*} \hat{w}_{N}(y) & = & \sum_{n=-\infty}^{\infty}w_{N}(n)e^{-i2\pi yTn}=\sum_{n=-\infty}^{\infty}w_{N}(n)e^{-i2\pi ln}=\sum_{n=-\infty}^{\infty}w_{N}(n)\\ & = & \sum_{n=-\frac{N-RT}{2T}}^{\frac{N-RT}{2T}}w_{N}(n)=\frac{N-RT}{T}+1=\frac{N+T(1-R)}{T} \end{eqnarray*}

We also know from the Poisson summation formula, that $\hat{w}_{N}(y)$ is equal to the periodic summation of $\hat{W}_{N}(y)$ at periods of $1/T$:

$$ \hat{w}_{N}(y)=\sum_{n=-\infty}^{n=\infty}\hat{W}_{N}(y-\frac{n}{T})=\begin{cases} N\sum_{n=-\infty}^{n=\infty}g\left(N(y-\frac{n}{T})\right)\end{cases} $$ as the sum of a periodically sinc function was defined above. This is precisely the definition of $f(k,y)$ above for $k=1/T$ and $N=1$, so plugging these into the general solution of

DTFT(y)=\begin{cases} N/T & yT\in\mathbb{Z},\,N/T\,\mathrm{even}\\ \frac{N+T(1-R)}{T} & yT\in\mathbb{Z},\,N/T\,\mathrm{not\,even}\\ \cos(\pi yN)+\frac{\sin(\pi y(N-T))}{\sin(\pi yT)} & yT\notin\mathbb{Z},\,N/T\,\mathrm{even}\\ \frac{\sin(\pi y(N+T(1-R))}{\sin(\pi yT)} & yT\notin\mathbb{Z},\,N/T\,\textrm{not}\,\mathrm{even} \end{cases}

where $R=NT/P\,\textrm{mod}\,2$ yields the summation is as given above.

  • $\begingroup$ I like this answer a lot as it gives a simple answer, but I am a bit "surprised" that it is much simpler than the other answers $\endgroup$ – Daniel May 15 '18 at 8:02
  • $\begingroup$ I believe the edited solution is now correct. I had previously defined the rectangular window to equal 1 on the interval [-N/2,N/2] rather than (-N/2,N/2) with value 1/2 at +/-N/2. With this correction, spot checks for values of k and y for which the sum can easily be computed explicitly check out; please let me know if you find any counterexamples or mistakes in the above. $\endgroup$ – Lauren Deason May 16 '18 at 3:54

$$f(k,y)=\sum_{n=-\infty}^{\infty} \frac{\sin \pi(kn-y)}{\pi(kn-y)}=\cos(\pi y)\sum_{n=-\infty}^{\infty} \frac{\sin (\pi kn)}{\pi(kn-y)}-\sin(\pi y)\sum_{n=-\infty}^{\infty} \frac{\cos (\pi kn)}{\pi(kn-y)}$$ $\sin(\pi kn)=0\quad$ and $\quad\cos(\pi kn)=(-1)^{kn}$ $$f(k,y)=-\sin(\pi y)\sum_{n=-\infty}^{\infty} \frac{(-1)^{kn}}{\pi(kn-y)}= \frac{\sin(\pi y)}{\pi k}\sum_{n=-\infty}^{\infty} \frac{(-1)^{kn}}{n-\frac{y}{k}}$$ $$\sum_{n=0}^{\infty} \frac{(-1)^{kn}}{n-\frac{y}{k}}=\Phi\left((-1)^k\:,\:1\:,\:-\frac{y}{k}\right)$$ $\Phi(z,s,a)$ is the Lerch function : http://mathworld.wolfram.com/LerchTranscendent.html $$\sum_{n=-\infty}^{0} \frac{(-1)^{kn}}{n-\frac{y}{k}}= \sum_{m=0}^{\infty} \frac{(-1)^{-km}}{-m+\frac{y}{k}} =-\Phi\left((-1)^k\:,\:1\:,\:\frac{y}{k}\right)$$ and the term for $n=0$ is equal to$\quad\frac{1}{0-\frac{y}{k}}=-\frac{k}{y}$ $$\sum_{n=-\infty}^{\infty} \frac{(-1)^{kn}}{n-\frac{y}{k}}=\Phi\left((-1)^k\:,\:1\:,\:-\frac{y}{k}\right)-\Phi\left((-1)^k\:,\:1\:,\:\frac{y}{k}\right)-\left(-\frac{k}{y}\right)$$ $$f(y,k)=-\frac{\sin(\pi y)}{\pi k}\left(\Phi\left((-1)^k\:,\:1\:,\:-\frac{y}{k}\right)-\Phi\left((-1)^k\:,\:1\:,\:\frac{y}{k}\right)+\frac{k}{y}\right)$$


If $\phi(t)$ is arbitrary function and $\Phi(\omega)$ its Fourier transform, then the following identity, known as Poisson's formula is true (see [1] pg.47): $$ \sum^{\infty}_{n=-\infty}\phi(t+nT)=\frac{1}{T}\sum^{\infty}_{n=-\infty}e^{2\pi i nt/T}\Phi\left(\frac{2\pi n}{T}\right)\textrm{, }T>0. $$

In the case of your's, the function $\phi(t)=\frac{\sin(at)}{t}$ have Fourier transform $\Phi(t)=\pi X_{[-a,a]}(t)$ ($X_{[-a,a]}(t)$ is the characteristic function in $[-a,a]$, $a>0$). Hence we get $$ \sum^{\infty}_{n=-\infty}\frac{\sin(a(t+n T))}{t+nT}=\frac{\pi}{T}\sum^{\infty}_{n=-\infty}e^{2\pi i n t/T}X_{[-a,a]}\left(\frac{2\pi n}{T}\right), $$ where $$ X_{[-a,a]}\left(\frac{2\pi n}{T}\right)=\left\{ \begin{array}{cc} 1,\textrm{ if }\left|\frac{2\pi n}{T}\right|\leq a\textrm{, for a certain }n\in\textbf{Z}\\ 0,\textrm{ otherwise } \end{array}\right\}. $$ Consequently we have $$ \sum^{\infty}_{n=-\infty}\frac{\sin(a(t+n T))}{t+nT}=\frac{\pi}{T}\sum_{|n|\leq aT/(2\pi)}e^{2\pi i n t/T}. $$

Hence if for example $a=5/2$, $T=3$, then $n=-1,0,1$ and $$ \sum^{\infty}_{n=-\infty}\frac{\sin(a(t+n T))}{t+nT}=\sum^{\infty}_{n=-\infty}\frac{\sin(\frac{5}{2}(t+2n))}{t+2n}= $$ $$ =e^{2\pi i (-1) t/3}+e^{2\pi i 0 t/3}+e^{2\pi i 1 t/3}=\frac{\pi}{3}\left(1+2\cos\left(\frac{2\pi t}{3}\right)\right). $$ Note that the Fourier transform $\Phi(x)$ of $\phi(t)$ is $$ \Phi(x)=\int^{\infty}_{-\infty}\phi(t)e^{-itx}dt $$


[1]: Athanasios Papoulis. ''The Fourier Integral and its Applications''. McGraw-Hill Book Company, Inc. United States of America, 1962

  • We have:

    $$f(k,y)=\sum_{n=-\infty}^{\infty} \frac{\text{sin} \pi(kn-y)}{\pi(kn-y)}$$

We consider first that $k$ is even, that means $\sin{(\pi kn-\pi y)}=\sin{(-\pi y)}$ no matter $n$

$f(k,y)=\frac{\sin(-\pi y)}{\pi}\sum_{n=-\infty}^{\infty} \frac{1}{(kn-y)}$

Let $\delta(n)=\frac{1}{(kn-y)}$, when $n=0$, $\delta=\frac{-1}{y}$

When $n$ is different than zero, $\delta(n)=\frac{1}{kn-y}$ if $n>0$, otherwise $\delta(x)=\frac{-1}{kx+y}$ where $x$ is positive and $n=-x$ which means, $\sum_{n=-\infty}^{\infty} \delta(n)=\frac{-1}{y}+\sum_{n=1}^{\infty}(\frac{1}{kn-y}-\frac{1}{kn+y})$

$$\sum_{n=1}^{\infty}(\frac{1}{kn-y}-\frac{1}{kn+y})=\left [\frac{1}{k}(ln(n-y/k)-ln(n+y/k))\right ]^\infty_1=\left [ \frac{1}{k}ln(\frac{n-y/k}{n+y/k})\right ]^\infty_1=\frac{1}{k}(ln1-ln(1-y/k)+ln(1+y/k))$$

The quantity is positive since $ln(k+y)>ln(k-y)$, that leads to:

$$f(k,y)=\frac{\sin(-\pi y)}{\pi}(\frac{-1}{y}+\frac{1}{k}ln(1+y/k)-\frac{1}{k}ln(1-y/k))$$

When $k$ is odd that leaves us with two sub-cases, $n=2l$ and $n=2l+1$.

Cases where $n=2l$ we call $f_{even}(k,y)=\frac{\sin(-\pi y)}{\pi}\sum_{n=-\infty}^{\infty} \frac{1}{(2kn-y)}$ because $\sin{(\pi kn-\pi y)}=\sin{(-\pi y)}$, Which gives the same first formula with $n$ substitued by $2n$.

If $n=2l+1$ , $\sin{(\pi kn-\pi y)}=\sin{(\pi y)}$ because $kn$ is odd.

In such case: $f_{odd}=\frac{\sin(\pi y)}{\pi}\sum_{n=1}^{\infty} (\frac{1}{k(2n+1)-y}-\frac{1}{k(2n+1)+y})$

Merging both cases; $f=f_{odd}+f_{even}$$$=\sin(-\pi y)\left [ \frac{-1}{y}+\frac{1}{2k}ln(\frac{n-y/2k}{n+y/2k})\right ]^\infty_1+\sin(\pi y)\left [ \frac{1}{2k}ln(\frac{n+(k-y)/2k}{n+(k+y)/2k})\right ]^\infty_0$$$$=\frac{\sin(-\pi y)}{\pi}(\frac{-1}{y}+\frac{1}{2k}ln(1+y/2k)-\frac{1}{2k}ln(1-y/2k))+\frac{\sin(\pi y)}{\pi}(\frac{1}{2k}ln(\frac{k+y}{2k})-\frac{1}{2k}ln(\frac{k-y}{2k}))$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.